Brainstem motor loops in the control of movement. - Nandi, D; Aziz, T; Liu, X; Stein, J (2002)
In recent years, the role of the area around the upper brainstem, particularly the pedunculopontine (PPN) region and the zona incerta (ZI), in the initiation and control of movement has generated much clinical interest. Using electrophysiological and pharmacological methods, we have further explored these structures and their influence in motor control in the nonhuman primate and in patients with proximal tremor. We have found that lesioning the PPN and electrical stimulation at high frequencies of the PPN region in the normal-behaving primate induces akinesia, and low frequency stimulation can induce tremor. In the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine hydrochloride (MPTP) -treated parkinsonian primate model, bicuculline, a gamma-aminobutyric acid antagonist, can alleviate akinesia when infused into the PPN region. Further studies will elucidate the possible clinical implications of these observations. The ZI has reciprocal connections with several cortical areas, the upper brainstem, cerebellum, and thalamus. We have found that chronic, high-frequency deep brain stimulation of the ZI suppresses proximal limb tremor. Field potential recordings from the ZI show significant coherence with concurrent proximal muscle electromyograms. This finding has potential clinical relevance as proximal tremor generally does not respond well to thalamic surgery and may be severely disabling.